Kajian tentang jenis umpan buatan pancing tonda terhadap hasil tangkapan - Billy Jehosua; Ivor L. Labaro; Lefrand Manoppo; Alfred Luasunaung; Johnny Budiman; Fanny Silooy (Universitas Sam Ratulangi, 2024)
The aim of this research is to determine the differences between two types of artificial bait on troll line on catches and to identify the composition of catch types based on bait type. This research was carried out in Tanawangko waters and was carried out from February to March 2023 using the experimental fishing method, where two pancing tonda each using silk fiber and chicken feather bait were operated simultaneously in one boat for 5 trips which were then analyzed using the t test. The catch during the research was 24 individuals with 3 species, namely with silk fiber bait, 20 individuals were caught consisting of 3 species and using chicken feather bait, 4 individuals were caught consisting of 2 species. The analysis results show that tcount = 1.684 < t table = 2.776; so it accepts H0 and rejects H1. This explains that the use of chicken feather bait is not significantly different from silk fiber as trolling bait for catch results. The conclusion of this research is that using silk fiber bait resulted in more catches than chicken feather bait, but the results of the t test analysis showed that the two were not significantly different and the three species of fish caught were 15 skipjack tuna (Katsuonus pelamis), 7 baby tuna (Thunnus sp.), and 2 lemadang (Coryphaena hippurus).